Stakeholders' Perception about Rice Knowledge Management Portal's information - Sunil Kumar, V. Sangeetha, Premlata Singh, R. Roy Burman, Arpan Bhowmik, (Indian Journal of Extension Education, 2018)
In agriculture various forces are working to change the agricultural extension from a process of technology transfer to a process of facilitating wide range of communication, information and advocacy services. The midsts of these change farmers are grappling with the question of how best to harness ICTs to benefit the farming. There was no scale available to measure farmers' perception towards knowledge portal. Ascale was constructed to measure the perception of the farmers towards Rice Knowledge Management Portal (RKMP). Likert's summated rating scale technique was followed for construction of perception scale. Out of 41 statements, 16 statements were retained on the final scale. The validity of the scale was examined with the help of content validity. Split half method was followed for testing reliability of the scale and reliability co-efficient of the scale was 0.76 hence, the scale is reliable and can produce consistent results. This scale can be used to measure farmers' perception beyond the study area with suitable modifications.